Subsequence Sums of Zero-sum-free Sequences - Yuan, Pingzhi (The Electronic Journal of Combinatorics, 2009)
Let $G$ be a finite abelian group, and let $S$ be a sequence of elements in $G$. Let $f(S)$ denote the number of elements in $G$ which can be expressed as the sum over a nonempty subsequence of $S$. In this paper, we slightly improve some results of Pixton on $f(S)$ and we show that for every zero-sum-free sequences $S$ over $G$ of length $|S|=\exp(G)+2$ satisfying $f(S)≥ 4\exp(G)-1$.